The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1073/pnas.0501589102
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic variation of the vomeronasal pheromone receptor gene repertoire among five orders of placental and marsupial mammals

Abstract: Pheromones are chemicals emitted and sensed by conspecifics to elicit social and sexual responses and are perceived in terrestrial vertebrates primarily by the vomeronasal organ (VNO). Pheromone receptors in the mammalian VNO are encoded by the V1R and V2R gene superfamilies. The V1R superfamily contains 187 and 102 putatively functional genes in the mouse and rat, respectively. To investigate whether this large repertoire size is typical among mammals with functional VNOs, we here describe the V1R repertoires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
211
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(222 citation statements)
references
References 64 publications
10
211
1
Order By: Relevance
“…1b ). The phylogenetic analysis revealed at least From Shi and Zhang (2007) e From Young and Trask (2007) f From Shi and Zhang (2006) h From Zhang et al (2007) i From Grus et al (2005) j From Niimura and Nei (2005) k From Niimura and Nei (2006) l From Alioto and Ngai (2005) m From n From Saraiva and Korsching (2007) nine ancestral OR genes (or gene lineages) in the most recent common ancestor (MRCA) of fishes and tetrapods (Niimura and Nei 2005) (Fig. 1b ).…”
Section: The or Gene Family -The Largest Gene Family In Mammalsmentioning
confidence: 99%
See 4 more Smart Citations
“…1b ). The phylogenetic analysis revealed at least From Shi and Zhang (2007) e From Young and Trask (2007) f From Shi and Zhang (2006) h From Zhang et al (2007) i From Grus et al (2005) j From Niimura and Nei (2005) k From Niimura and Nei (2006) l From Alioto and Ngai (2005) m From n From Saraiva and Korsching (2007) nine ancestral OR genes (or gene lineages) in the most recent common ancestor (MRCA) of fishes and tetrapods (Niimura and Nei 2005) (Fig. 1b ).…”
Section: The or Gene Family -The Largest Gene Family In Mammalsmentioning
confidence: 99%
“…However, the functional V1R repertoire is small, with only four open reading frames in most individuals Zhang and Webb 2003) . Grus et al (2005) identified functional V1R genes from five orders of placental and marsupial mammals ( Table 1 ). The intact V1R repertoire size varies by at least 23-fold among mammals with functional VNOs and this size ratio represents the greatest among-species variation in gene family size of all A more recent study found that the platypus, a semiaquatic monotreme, has the largest V1R repertoire characterized to date, with 270 potentially functional genes and 579 pseudogenes.…”
Section: The V1r Gene Family -The Family With the Highest Among-specimentioning
confidence: 99%
See 3 more Smart Citations